High Frequency of Non-nocturnal Hypoglycemia was Associated with Poor Sleep Quality Measure by Pittsburg Sleep Quality Index in Patients with Diabetes Receiving Insulin Therapy: Diabetes Distress and Care Registry at Tenri (DDCRT 4) - Hayashino, Y.; Tsujii, S.; Ishii, H.; null (Experimental and Clinical Endocrinology & Diabetes, 2013)
To investigate the temporal association between frequency of non-nocturnal hypoglycemia and sleep quality among patients with diabetes receiving insulin therapy.We used data from 1 513 patients with diabetes receiving insulin therapy. We estimated the relative risks (RR) of the frequency of non-nocturnal hypoglycemia for poor sleep quality measured by the Pittsburgh Sleep Quality Index.The average age and HbA1c value of the patients were 63.7 years and 7.8%, respectively. Compared with poor sleep quality in patients without any type of non-nocturnal disabling hypoglycemia (NNDH), the multivariable-adjusted RR values for poor sleep quality were 1.30 (95% confidence interval [CI], 1.06–1.61) and 1.37 (95% CI, 0.96–1.95) in patients who experienced 1–4 and ≥5 episodes of NNDH, respectively (p=0.004). Experiencing non-nocturnal severe hypoglycemia (NNSH) once in the past 90 days significantly increased the risk of poor sleep quality by 1.54 episodes (95% CI, 1.16–2.05; p=0.003). By adding the presence of depression as a variable to the multivariable-adjusted model, these associations were attenuated because we did not observe any significant association between NNDH and poor sleep quality (p=0.178). However, a significant association between NNSH and poor sleep quality was observed (RR=1.43; 95% CI, 1.09–1.90; p=0.011).A high frequency of non-nocturnal hypoglycemia was associated with poor sleep quality in patients with diabetes receiving insulin therapy. Our data also suggested that the association of NNDH, and not NNSH, was mediated by comorbid depression.
Keywords: diabetes; autoimmunity; hypoglycemia; sleep